2022
DOI: 10.3390/polym14050975
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Polymer Composites: A Role of Transfer Films in Ensuring Tribological Properties—A Review

Abstract: The purpose of this review is to summarize data on the structure, mechanical and tribological properties, and wear patterns of composites based on high-performance polymers (HPPs) intended for use in friction units. The review includes three key sections, divided according to the tribological contact schemes regardless of the polymer matrix. In the second part, the analysis of composites is carried out in point contacts. The third section is devoted to the results of studies of HPP-based composites in linear o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 170 publications
4
7
0
Order By: Relevance
“…Besides, one can observe a relatively smooth and compact worn surface, which is in good accordance with the desirable reduced coefficient of friction and improved wear resistance of the BGF/TiO 2 /PI nanocomposite. Again, one can agree to this as study by Ali et al 68 and Panin et al 69 revealed that good tribological behaviour of polymer materials can be obtain with nanofillers incorporation. And such is the case in the present study of the composite filled with TiO 2 nanoparticles.
Figure 3.(a) Coefficient of friction and (b) Wear rate of the neat PI and reinforced PI composites under dry sliding conditions of load 10 N and sliding speed 200 r/min).
Figure 4.Optical micrograph of the samples wear track; (a) Neat PI, (b) BGF/PI, and (c) BGF/TiO 2 /PI composite.
…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Besides, one can observe a relatively smooth and compact worn surface, which is in good accordance with the desirable reduced coefficient of friction and improved wear resistance of the BGF/TiO 2 /PI nanocomposite. Again, one can agree to this as study by Ali et al 68 and Panin et al 69 revealed that good tribological behaviour of polymer materials can be obtain with nanofillers incorporation. And such is the case in the present study of the composite filled with TiO 2 nanoparticles.
Figure 3.(a) Coefficient of friction and (b) Wear rate of the neat PI and reinforced PI composites under dry sliding conditions of load 10 N and sliding speed 200 r/min).
Figure 4.Optical micrograph of the samples wear track; (a) Neat PI, (b) BGF/PI, and (c) BGF/TiO 2 /PI composite.
…”
Section: Resultssupporting
confidence: 76%
“…Besides, one can observe a relatively smooth and compact worn surface, which is in good accordance with the desirable reduced coefficient of friction and improved wear resistance of the BGF/TiO 2 /PI nanocomposite. Again, one can agree to this as study by Ali et al 68 and Panin et al 69 revealed that good tribological behaviour of polymer materials can be obtain with nanofillers incorporation. And such is the case in the present study of the composite filled with TiO 2 nanoparticles.…”
Section: Mechanical Propertiessupporting
confidence: 76%
“…In addition to the type and amount of fillers, as well as the test temperature, many factors affected the CoF and WR values. However, the results were actually determined by the regularities of the TF formation, adhering and degradation [ 35 ]. Among the key influencing factors, the following should be noted: the sliding speed, normal load, environmental temperature, surface roughness, counterpart material, polymer structure, types of both fillers and lubricating medium (if any), etc.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the tests were carried out under equal conditions. In this work, a comparison of the TF formation patterns was carried out for three-component PI- and PEI-composites under mild tribological loading conditions at a point contact (ball-on-disk, P = 5 N, V = 0.3 m/s) at room and elevated temperatures, despite the fact that the PTFE, Gr, and MoS 2 solid lubricant mechanism was described in the literature [ 35 ]. To the best of our knowledge, this was not performed in a similar formulation before.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, type of reinforcement, weight percentage, friction contact area and lubrication influences the friction resistance of polymer composites. [ 53 ] Figure 12 shows the COF change for all structures over the test duration at different speeds for alumina reinforced PLA material. The cause of friction for polymers and its composites are due to adhesion, deformation and elastic hysteresis.…”
Section: Application To Biomedical Structure: Case Studymentioning
confidence: 99%